2022
DOI: 10.2147/ndt.s374549
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke in the Context of SARS-CoV-2 Vaccination: A Systematic Review

Abstract: Background There have been reports suggesting an increased incidence of acute ischemic stroke among anti-SARS-CoV-2 vaccinees. We aimed to systematically review the literature to summarize the available evidence on the association between SARS-CoV-2 vaccination and acute ischemic stroke. Methods A systematic literature search on MEDLINE, LitCovid and LIVIVO databases was performed for eligible randomized controlled trials, observational studies, registries and case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…SC2V-related cerebrovascular diseases include VST, ischemic stroke, ICH, SAB, pituitary apoplexy, RCVS, cerebral vasculitis, and Susac syndrome ( Table 2 ) [ 4 , 6 …”
Section: Resultsmentioning
confidence: 99%
“…SC2V-related cerebrovascular diseases include VST, ischemic stroke, ICH, SAB, pituitary apoplexy, RCVS, cerebral vasculitis, and Susac syndrome ( Table 2 ) [ 4 , 6 …”
Section: Resultsmentioning
confidence: 99%
“…The long time interval in our study also included the vaccination program that started in the first half of 2021 in our country. Although complications especially ASIS and CVST have been reported post-COVID-19 vaccination, Rahming et al reported in their review that there was no significant increase in the overall incidence of stroke in the population of individuals administered COVID-19 vaccines 39 . According to our results, we thought that the main cause of positive neuroimaging in our patients who were COVID-19 positive before vaccination and who were vaccinated afterward was the infection itself.…”
Section: Discussionmentioning
confidence: 96%
“…Appearance of persistent or unusual neurological symptoms following SARS-CoV-2 vaccine should be urgently investigated for VITT. 25 In meta-analytic studies, acute ischemic stroke (AIS) was reported in 4.7 cases per 100,000 vaccinations, 26,27 which is comparable to its prevalence in the general population.…”
Section: Acute Ischemic Strokementioning
confidence: 99%